PENYULUHAN CARA PENGGUNAAN OBAT KONVENSIONAL DAN OBAT TRADISIONAL DESA TANJUNG PUTRA BATANGHARI JAMBI - Andriani, Medi; Sanuddin, Mukhlis; yuliandani, yuliandani; Putri, Elfiana Meirela (Universitas Baiturrahim, 2024)
Conventional medicines are medicines that use synthetic or inorganic materials, are antibiotics (kill cancer) and can only treat symptoms of disease and can cause side effects. Traditional medicine is a material or concoction of ingredients in the form of plant materials, animal materials, mineral materials, galenic preparations or mixtures of these materials which have been used for generations for treatment, and can be applied in accordance with the norms applicable in communities that have little side effects. Providing information to the public about how to use conventional and traditional medicines. Lecture, question and answer, and pamphlet methods. Information about long-term deadly diseases that make people aware of the importance of using both conventional and traditional medicines.